Influence of parental factors on upper basic students’ performance in Social and Islamic Studies in Ilorin, Nigeria - Olokooba, Issa Nasiru; Owoyale-Abdulganiy, Ibrahim Solahudeen (International Journal of Educational Innovation and Research, 2022)
Parenting is the process of promoting and supporting the physical, emotional, social, and intellectual development of a child from infancy to adulthood. The study therefore examined the influence of parental factors on upper basic students’ academic performance in Social and Islamic Studies in Ilorin, Nigeria. A descriptive survey research design was adopted for the study. The sample for this study was all upper basic Social and Islamic Studies students in Ilorin. Systematic random sampling was employed to select seven upper basic schools in Ilorin. Purposive sampling technique was used to select 180 upper basic 2 Social and Islamic Studies students. A Pro-Forma was used as the instrument for data collection. Data analysis was done using ANOVA and Scheffe-Post Hoc analysis for research hypotheses. The result of the study showed that there was a significant difference in the academic performance of upper basic students’ in Social and Islamic Studies based on parental educational level and Socio-economic Status, the parental educational level. The finding of the study revealed that there was no significant difference in the academic performance of upper basic students’ in Social and Islamic Studies based on parental occupation and marital status. Based on these findings, it was recommended among other that parents should create enough time with their children especially in the area of communication concerning school activities, expectations of academic performance, the importance of achieving good results and they should always ask, and give encouragement to the children about the importance of homework.